1998
DOI: 10.1002/(sici)1097-4628(19980725)69:4<695::aid-app8>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of UV-curable waterborne unsaturated polyester for wood coating

Abstract: UV-curable waterborne unsaturated polyesters for wood coatings were prepared. The effects of different polyols and acids on the properties of the UV-curable waterborne unsaturated polyesters were investigated. Several different unsaturated polyester prepolymers were prepared from three different polyols [ethylene glycol (EG), diethylene glycol (DEG), and propylene glycol (PG)] and three different acids [tetrahydrophthalic anhydride (THPAn), terephthalic acid (TPA), and trimellic anhydride (TMAn)]. UV-curable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 1 publication
2
23
0
2
Order By: Relevance
“…Crosslinking density is strongly dependent on the exposure time, the wavelength of the light, the type of photoinitiator, as well as the reactivity of monomers. In general, increasing the crosslinking density of the polymers increases the strength of cured polymers (Ha et al, 1996;Jung et al, 1998). In terms of the crosslinking density, the PPF used in the present research was not purified, and so some unreacting materials could have remained in solution, and these materials did not participate in crosslinking, and thus, reduced the crosslinking density (Varadan et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Crosslinking density is strongly dependent on the exposure time, the wavelength of the light, the type of photoinitiator, as well as the reactivity of monomers. In general, increasing the crosslinking density of the polymers increases the strength of cured polymers (Ha et al, 1996;Jung et al, 1998). In terms of the crosslinking density, the PPF used in the present research was not purified, and so some unreacting materials could have remained in solution, and these materials did not participate in crosslinking, and thus, reduced the crosslinking density (Varadan et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…That is, on increasing the molecular weight of polymers, the polymers are more difficult to use in manufacturing due to an increased melt viscosity (Menon et al, 2002), despite the strength of the polymer increasing with viscosity. The manufacturability of polymers is further impacted by the molecular weight distribution within the polymer (Ha et al, 1996;Jung et al, 1998). The DEF content used in this work was fixed at 30%, similar to that used in the work of Fisher et al (2002b), because Fisher et al showed that a solution of PPF with 30% (w/w) of DEF had the highest elastic modulus and fracture strength.…”
Section: Discussionmentioning
confidence: 99%
“…不饱和聚酯因价格低廉、加工容易和应用灵活 [1][2][3] ,而备受关注的一类工业化热固性树脂,它可应用 于片材、建筑材料、粘胶剂、涂料,且在建筑行业和 电子工业也发挥着重要作用 [4][5][6] 。 通常不饱和聚酯是由 二元醇、马来酸酐和其它二元酸缩聚反应制备而成, 合成方法灵活,原料来源广 [7][8][9] 。尽管不饱和聚酯拥有 众多优点,可室温储存、室温固化、低密度、材料透 明和绝缘 [10] ;但传统不饱和聚酯也存在某些缺点,相 应材料通常强度不高、韧性差、耐酸碱老化性差、易 燃 [11] 。大量文献报道,通过两种方法可改善传统不饱 和聚酯材料的性能。方法一:通过化学合成方法,在 不饱和聚酯分子链引入特殊基团,提高相应材料力学 性能或耐酸、碱老化性。在不饱和聚酯分子链结构上, 通过化学共价键引入丙烯酸酯基团 [12] 或双环戊二烯 结构 [13] 氢氧化铝颗粒对改性不饱和聚酯性能的影响 填充无机填料或化学助剂。适量的纳米二氧化硅、蒙 脱土和短丝纤维提高了不饱和聚酯的力学及热稳定 性 [14][15][16][17][18] …”
Section: 引言unclassified
“…Compared with the conventional thermal drying process, coatings which are cured by UV have many advantages, such as fast curing, energy saving, low solvent release and so on. The major compositions of UVcurable coatings are organic oligomer, reactive monomer, photo-initiator and various additives [1][2][3]. By adjusting the ingredient and content of the major compositions, UV-curable coatings with various properties can be obtained, which are widely used as surface protection of materials such as plastics, metals, glasses, fabrics, etc.…”
Section: Introductionmentioning
confidence: 99%